1970
DOI: 10.1007/bf00193903
|View full text |Cite
|
Sign up to set email alerts
|

Problems of atmospheric shear flows and their laboratory simulation

Abstract: Shear flows generated by movement of the atmosphere near the earth's surface are accompanied by complexities not ordinarily encountered in the treatment of turbulent boundary layers. Problems arising from the following physical features are considered:(1) thermal stratification;(2) surface roughness in the form of forests and cities;(3) non-uniformity of surface roughness and/or temperature (leading to 3-dimensional turbulent boundary layers);(4) surface irregularities in the form of hilly and mountainous topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Intermediate‐scale experimentation was originally introduced in the early 1990s and has been extensively adopted at CESEP for studying the fate and transport behavior of nonaqueous phase liquids [e.g., Illangasekare et al ., ; Barth et al ., ; Moreno‐Barbero and Illangasekare , ] and CO 2 leakage, exsolution, and trapping [e.g., Plampin et al ., ; Trevisan et al ., ; Agartan et al ., ]. According to the definition provided above, wind tunnel testing can also be considered a form of intermediate‐scale testing; wind tunnels have historically been employed in the investigation of the atmospheric boundary layer development [e.g., Cermak and Arya , ; Cermak , ; Burton , ], atmospheric gas dispersion [e.g., Meroney and Neff , ; Michioka et al ., ], and wind erosion of soils and dune formation [e.g., Bagnold , ; Gabriels et al ., ]. Haghighi and Or [, ] and Trautz [], among others, have further demonstrated that intermediate‐scale experimentation can be adopted with great success for studying a class of problems related to coupled porous media‐free flow systems (e.g., bare‐soil evaporation).…”
Section: Experimental Design Conceptsmentioning
confidence: 99%
“…Intermediate‐scale experimentation was originally introduced in the early 1990s and has been extensively adopted at CESEP for studying the fate and transport behavior of nonaqueous phase liquids [e.g., Illangasekare et al ., ; Barth et al ., ; Moreno‐Barbero and Illangasekare , ] and CO 2 leakage, exsolution, and trapping [e.g., Plampin et al ., ; Trevisan et al ., ; Agartan et al ., ]. According to the definition provided above, wind tunnel testing can also be considered a form of intermediate‐scale testing; wind tunnels have historically been employed in the investigation of the atmospheric boundary layer development [e.g., Cermak and Arya , ; Cermak , ; Burton , ], atmospheric gas dispersion [e.g., Meroney and Neff , ; Michioka et al ., ], and wind erosion of soils and dune formation [e.g., Bagnold , ; Gabriels et al ., ]. Haghighi and Or [, ] and Trautz [], among others, have further demonstrated that intermediate‐scale experimentation can be adopted with great success for studying a class of problems related to coupled porous media‐free flow systems (e.g., bare‐soil evaporation).…”
Section: Experimental Design Conceptsmentioning
confidence: 99%
“…Among others, it is desirable to reproduce the wind profile in the test section. Cermak and Arya [14], like other authors, state that "to satisfy, even approximately, the various criteria of similarity between atmospheric shear flows and simulated flows in wind tunnels, thick turbulent boundary layers with large turbulence intensities are required". To appropriately model the boundary layer in a wind tunnel, a long roughened surface would be necessary.…”
Section: Incoming Velocity Profile and Similarity Criteriamentioning
confidence: 98%
“…It is di cult to apply the results of laboratory experiments, conducted in controlled conditions, to the complex conditions found in the PBL. Indeed the PBL does not usually have a w ell-de ned outer edge, as do laboratory ows (Cermak and Arya, 1970). Laboratory conditions may allow study of selected processes at low Reynolds number.…”
Section: Limitations Of Laboratory Studiesmentioning
confidence: 99%